Unconventional Narrative Structure and The Problem of Latency Phase in Peter Pan Novel - Elve Oktafiyani; Diva Salsabila Anindita (Buletin Al-Turas, 2022)
PurposeThis research aimed to explain the human’s latency phase through child characters in Peter Pan novel and its relation to the novel unconventional narrative structure. MethodThe research was qualitative using a descriptive case design. The novel’s intrinsic elements were analyzed to see the complexity of this children's literature that led to the analysis of the latency phase of the child characters through the make-believe play. The analysis made uses of Sigmund Freud’s concept of psychosexual personality development. Results/FindingsThis research found that the novel’s complexity came from its unconventional narrative structure such as the layered sub-plots, unique settings, and characters with complex personalities that were uncommon in children’s literature. It then led to the further analysis of the children who were processing their latency phase through their activities. Focusing on Peter as a captain and a father and Wendy as a mother, all the roles manifested their wishes and desires. ConclusionThe research concluded that the unique, inconsistent, and illogical points from the unconventional narrative structure could be explained through the analysis of the story’s issue about the latency phase, which shows complexity found despite its status as children’s literature.